EFEK PEMODERASI KURS RUPIAH DALAM MODEL STRUKTURAL PENGARUH STRUKTUR MODAL DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN DI BEI - Iskandar Zulkarnaein (The Manager Review, 2019)
The objective of this research is to determine the effect of foreign exchange rate(IDR) as moderator variable in the influence of capital structure and dividend policy onStock Prices of companies at IDX. In this research samples are 45 companies as the mainmover of Indonesia Stock Indices. This research uses Panel Data Analysis (PDA) to test thehypotheses. The results show that: (1) capital structure (debt equity ratio) and dividendpayout ratio have a significance influence on the stock price and the stock market, (2)exchange rate (US$/IDR) has negative moderating effect on both capital structure anddividend payout ratio. In conclusion, this research support the theory of capital structureand dividend relevance, even in bear market in Indonesia. The decreasing IDR agains US $causes the influence of capital strucure and dividend policy on both the composite stockindex and the stock prices.